دور العناقيد الصناعية في خلق القيمة المشتركة في المؤسسة الاقتصادية-دراسة حالة في مؤسسة الورود الوادي - - ابتسام فقيري; نهاد بوحنية; هنادي بن فرحات (جامعة الوادي University Of Eloued, 2024)
"تهدف هذه الدراسة إلى توضيح مدى مساهمة العناقيد الصناعية في خلق القيمة المشتركة في المؤسسة الاقتصادية "" دراسة حالة مؤسسة الورود بالوادي "" ، حيث اعتمدنا على المنهج الوصفي التحليلي، و تم اختيار عينة مكونة من 40 عامل بالمؤسسة لإجراء الدراسة الميدانية ، تمت الدراسة في فترة من 29 فيفري إلى 20 ماي، والتي تم الاعتماد فيها على الاستبيان كأداة لجمع البيانات والمعلومات ، و توصلت الدراسة إلى النتائج التالية : آليات العناقيد الصناعية التي تدعم خلق القيمة المشتركة في مؤسسة الورود في التركيز الجغرافي، التخصص الابتكار التعاون ، المنافسة ) ، يتم اعتماد أبعاد القيمة المشتركة المؤسسة الورود محل الدراسة بنسب متساوية، هناك اثر ذو دلالة إحصائية الأبعاد العناقيد الصناعية على القيمة المشتركة ، هناك اثر ذو دلالة إحصائية الأبعاد العناقيد الصناعية على القيمة الاقتصادية، هناك اثر الأبعاد العناقيد الصناعية على القيمة الاجتماعية في مؤسسة الورود الوادي . " "The aim of this study is to illustrate the extent of industrial clusters contribution to creating shared value in the economic enterprise"" Case Study of Al- Wurud Company in El Oued"" The study adopted the descriptive-analytical method and selected a sample ofany to conduct 40 the field study. The study was conducted from February29 to May 20 and a questionnaire was used as a tool for data and information collection, The study reached the following conclusions: The mechanisms of industrial clucters that support the creation of shard value in the roses foundation under study are (geographical concentration, specialization, innovation, cooperation, competition), the dimensions of shared value in the roses foundation under study were adopted at higher percentage for social value, There is a statistically significant impact of the dimensions of industrial clusters on shared value, there is a statistically significant impact of the dimensions of industrial clusters on economic value,, and there is an impact of the dimensions of industrial clusters on social value in Al-Wurud Company in El Oued."
Keywords: قيمة مشتركة ، خلق قيمة مشتركة ، مسؤولية اجتماعية ، عناقيد صناعية .; Shared value; creating shared value; social responsibility; industrial clusters